Fluid-induced breakdown of white mica controls nitrogen transfer during fluid–rock interaction in subduction zones. Issue 5 (26th April 2017) - Halama, Ralf; Bebout, Gray E.; Marschall, Horst R.; John, Timm
ABSTRACT: In order to determine the effects of fluid–rock interaction on nitrogen elemental and isotopic systematics in high-pressure metamorphic rocks, we investigated three different profiles representing three distinct scenarios of metasomatic overprinting. A profile from the Chinese Tianshan (ultra)high-pressure–low-temperature metamorphic belt represents a prograde, fluid-induced blueschist–eclogite transformation. This profile shows a systematic decrease in N concentrations from the host blueschist (~26 μg/g) via a blueschist–eclogite transition zone (19–23 μg/g) and an eclogitic selvage (12–16 μg/g) towards the former fluid pathway. Eclogites and blueschists show only a small variation in δ 15 Nair (+2.1 ± 0.3‰), but the systematic trend with distance is consistent with a batch devolatilization process. A second profile from the Tianshan represents a retrograde eclogite–blueschist transition. It shows increasing, but more scattered, N concentrations from the eclogite towards the blueschist and an unsystematic variation in δ 15 N values (δ 15 N = + 1.0 to +5.4‰). A third profile from the high- P/T metamorphic basement complex of the Southern Armorican Massif (Vendée, France) comprises a sequence from an eclogite lens via retrogressed eclogite and amphibolite into metasedimentary country rock gneisses. Metasedimentary gneisses have high N contents (14–52 μg/g) and positive δ 15 N values (+2.9 to +5.8‰), and N concentrations become lower away from the contact with 11–24 μg/g for the amphibolites, 10–14 μg/g for the retrogressed eclogite, and 2.1–3.6 μg/g for the pristine eclogite, which also has the lightest N isotopic compositions (δ 15 N = + 2.1 to +3.6‰). Overall, geochemical correlations demonstrate that phengitic white mica is the major host of N in metamorphosed mafic rocks. During fluid-induced metamorphic overprint, both abundances and isotopic composition of N are controlled by the stability and presence of white mica. Phengite breakdown in high- P/T metamorphic rocks can liberate significant amounts of N into the fluid. Due to the sensitivity of the N isotope system to a sedimentary signature, it can be used to trace the extent of N transport during metasomatic processes. The Vendée profile demonstrates that this process occurs over several tens of metres and affects both N concentrations and N isotopic compositions.